The state of Sombre Tit Poecile lugubris Temminck, 1820 in Armenia (Avocetta, 2024)
The Sombre Tit Poecile lugubris is very little studied species, and within Armenia, it occurs only in the south-eastern regions of the country. The current study aims at providing data for the next assessment of the conservation status of Sombre Tit in Armenia, based on the data collected from 2003-2019. The obtained data show that Sombre Tits have slightly expanded their distribution to the north; their current Area of Occupancy makes 94 km2, while the Extent of Occurrence covers 1,065 km2. The population of Sombre Tit makes from 910 to 1,350 breeding pairs. During observed 17 years (2003-2019), the population trend of the species computed for the Meghri region of Armenia can be considered stable (Imputed Overall Slope: Additive = 0.0017 ± 0.0109; Multiplicative = 1.0017 ± 0.0109; P > 0.05), although demonstrates relatively strong fluctuations. The conservation status of Sombre Tit in Armenia should be revised, as it can correspond to the category Endangered, according to criteria C2a(ii). The main factors that can influence the species in Armenia are forest fires, which are relatively common in south-eastern Armenia, and the use of pesticides for forest pest control.
Keywords: Sombre Tit; Poecile lugubris; Armenia; Conservation status; Population dynamics; Threats